Special measures' applications for victims and vulnerable and intimidated witnesses: the way forward / Abidah Abdul Ghafar - Abdul Ghafar, Abidah (2014)
Special treatment for victims and vulnerable and intimidated witnesses (VIWs) in a criminal process has developed over time in the United Kingdom, United States and Australia. This development has initiated the use of special measures‟ application in courts proceedings. In those countries, some measures to lessen stress and trauma of such witnesses undergoing a criminal process were introduced into the legislations. Yet, as many other Asian countries, Malaysia developed her victims‟ policy only in 1990s and issues relating to the protection of VIWs were raised within the criminal justice system a few years back. The tendency to put the standpoint into practice in the Malaysian legal system is demonstrated in the establishment of the Evidence of Child Witness Act 2007 (ECWA 2007) and the amendment of Section 272B of the Criminal Procedure Code. This paper aims at evaluating the current position of victims‟ and VIWs‟ rights and legal protection in the Malaysian criminal justice process. It elaborates on the rights of victims and other VIWs to special measures‟ applications in the court proceedings such as live TV-link, screens, removal of formal attire, intermediaries and visual aids communication. It advocates for the potential of special measures‟ application to accommodate victims‟ and VIWs to give testimony in court. The feasibility of video-recorded evidence as one of the means to facilitate traumatized victims and VIWs to give evidence and testimony in courts is also advocated in this paper.